Work Status and Return to the Workforce after Coronary Artery Bypass Grafting and/or Heart Valve Surgery: A One-Year-Follow Up Study. (14th June 2014) - Fonager, Kirsten; Lundbye-Christensen, Søren; Andreasen, Jan Jesper; Futtrup, Mikkel; Christensen, Anette Luther; Ahmad, Khalil; Nørgaard, Martin Agge
Abstract : Background . Several characteristics appear to be important for estimating the likelihood of reentering the workforce after surgery. The aim of the present study was to describe work status in a two-year time period around the time of cardiac surgery and estimate the probability of returning to the workforce. Methods . We included 681 patients undergoing coronary artery bypass grafting and/or heart valve procedures from 2003 to 2007 in the North Denmark Region. We linked hospital data to data in the DREAM database which holds information of everyone receiving social benefits. Results . At the time of surgery 17.3% were allocated disability pension and 2.3% were allocated a permanent part-time benefit. Being unemployed one year before surgery reduced the likelihood of return to the workforce (R R = 0.74 (0.60–0.92)) whereas unemployment at the time of surgery had no impact on return to the workforce (R R = 0.96 (0.78–1.18)). Sickness absence before surgery reduced the likelihood of return to the workforce. Conclusion . This study found the work status before surgery to be associated with the likelihood of return to the workforce within one year after surgery. Before surgery one-fifth of the population either was allocated disability pension or received a permanent part-time benefit.